2015
DOI: 10.5114/jcb.2015.53525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of permanent 125 I seeds implants with two different techniques in 500 cases of prostate cancer

Abstract: PurposeTo perform a comparative study of 500 consecutive 125I seeds implants for intracapsular prostate carcinoma with two techniques differing in terms of both strand implantation and planning.Material and methodsFrom 2002 to 2007 we performed 250 implants with fixed stranded seeds (RapidStrand™) and a preplanning system and from 2007 to 2010, 250 with real-time and ProLink™ system. Mean age was 68 and 66, respectively, median PSA (prostate-specific antigen) 7.3 and 7.2, stage T1-T2a in 98% and 94%, and Gleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…Biochemical failure is often used as a reliable marker for treatment efficacy and prostate cancer survival. Several studies have shown that the primary pre-treatment factors associated with PSA control are pre-treatment PSA, the Gleason score, and the clinical stage [4, 5, 21]. This makes PSA control comparisons across single-institution series problematic because case selection will have a significant impact on the outcome of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical failure is often used as a reliable marker for treatment efficacy and prostate cancer survival. Several studies have shown that the primary pre-treatment factors associated with PSA control are pre-treatment PSA, the Gleason score, and the clinical stage [4, 5, 21]. This makes PSA control comparisons across single-institution series problematic because case selection will have a significant impact on the outcome of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports with long term follow-ups are now available, which confirm good outcomes in selected patients with prostate specific antigen (PSA), relapse-free survival rates equivalent to those achieved by surgery [2, 3]. However, the excellent results achieved with both low and high dose rate brachytherapy mostly come from single institutions in developed countries with significant experience in prostate brachytherapy [4, 5]. Setting up of a prostate brachytherapy service requires expensive equipment [6] and well trained personnel; therefore not surprisingly there have been relatively few reports from Africa [7].…”
Section: Purposementioning
confidence: 99%
“…With this approach, the user can create intraoperatively built custom linked seeds, using a combination of seeds, connectors, and spacers. The advantages of linked seeds include intraoperative customization, less migration, and increased stabilization due to linking, indicating the benefits of loose plus stranded seeds [ 18 ].…”
Section: Purposementioning
confidence: 99%
“…Firstly, the seeds can deliver a high radiation dose to the target tissues that drops rapidly with the distance from the seeds, thereby resulting in low radiation doses to the surrounding tissues. As a result, the use of 125 I seeds enables the delivery of a high radiation dose to tumor tissues while minimizing injury to normal tissues, which requires less shield [ 9 ]. For example, cumulative absorbed dose at the 5 mm from the source axis was 97.2 Gy and it dropped rapidly to 28.8 Gy at the 10 mm from the source axis in this patient.…”
Section: Discussionmentioning
confidence: 99%